A kid's guide to staying safe around water - Boelts, Maribeth, 1964- (New York : Rosen Publishing Group's PowerKids Press, 1997)
Provides advice on how to remain safe in and around swimming pools, lakes, and oceans.
Includes index.
3 6 13 29 30
Keywords: Aquatic sports -- Safety measures; Aquatic sports -- Safety measures -- Juvenile literature; Safety